2017
DOI: 10.1016/j.bpj.2016.11.225
|View full text |Cite
|
Sign up to set email alerts
|

SK4 Ca 2+ -Activated K + Channels Regulate Sinoatrial Node Firing Rate and Cardiac Pacing In Vivo

Abstract: proteins assembly, but the previous experiments did not include Syt1. In our set up, both surfaces are coated with a lipid bilayer. One of them mimics the synaptic vesicle membrane, on which we bind Syt1. The opposing bilayer mimics the inner leaflet of the plasma membrane and contains PIP2 and PS lipids. We will present results obtained with various lipid compositions and relevant mutations of the protein and how these interactions are impacted by the presence of calcium. Ultimately, we plan to provide a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These channels are also expressed in the AVN and sinoatrial node (SAN) (4-6). Previous studies have demonstrated that SK4 inhibitors can lower the frequency of action potentials of the SAN (5-7), whereas mathematical models have predicted that the upregulation of SK4 would increase the automaticity of SAN cells (5,8).…”
Section: Introductionmentioning
confidence: 99%
“…These channels are also expressed in the AVN and sinoatrial node (SAN) (4-6). Previous studies have demonstrated that SK4 inhibitors can lower the frequency of action potentials of the SAN (5-7), whereas mathematical models have predicted that the upregulation of SK4 would increase the automaticity of SAN cells (5,8).…”
Section: Introductionmentioning
confidence: 99%